The Rock Garden - (:unkn) unknown (Pereira and Co., Ltd., Port of Spain, Trinidad, 2009)
A picture of two persons watching a child play near the waters edge of the pond in the Rock Garden, Queen's Park Savannah, Port of Spain, Trinidad. The pond is covered with water lilies and in the background are a variety of colourful tropical plants. Affixed to the back of the postcard are two Trinidad and Tobago stamps, a 2 cents and a 6 cents. Postcard number P59532.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Rock gardens--Trinidad and Tobago; Ponds--Trinidad and Tobago; Water lilies--Trinidad and Tobago; 1969; Aquatic plants--Trinidad and Tobago; Children--Trinidad and Tobago; Recreation--Trinidad and Tobago; Outdoor recreation--Trinidad and Tobago; Plants--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Queen's Park Savannah (Port of Spain)